Estimation of surface downward shortwave radiation over China from AVHRR data based on four machine learning methods. (1st January 2019) - Wei, Yu; Zhang, Xiaotong; Hou, Ning; Zhang, Weiyu; Jia, Kun; Yao, Yunjun
Highlights: Four machine learning methods were used to estimate downward shortwave radiation. GBRT is an efficient method to estimate downward shortwave radiation. The DSR estimates based on GBRT has similar spatial distributions with CERES-EBAF. The DSR estimates based on the GBRT does not show overestimation tendency. Abstract: Downward shortwave radiation ( DSR ) is one of the major driving forces of climate system. Knowledge of the Earth's radiation budget is essential for improving our understanding of the Earth's climate. Therefore, accurate estimation of DSR has great significance. Satellite remote sensing is a practical way to derive DSR with high spatial resolution and coverage. In this study, four machine learning methods, including gradient boosting regression tree (GBRT), random forest (RF), multivariate adaptive regression spline (MARS), and artificial neural network (ANN), were applied to estimate DSR at a spatial resolution of 5 km and a temporal resolution of 1 day using Advanced Very High Resolution Radiometer (AVHRR) data. The DSR estimates based on four machine learning methods were evaluated using ground measurements at 96 sites over China. The measurements were collected from the Climate Data Center of the Chinese Meteorological Administration (CDC/CMA) from 2001 to 2003. The evaluation results showed that the GBRT method performed best at both daily and monthly time scales under both clear and cloudy sky conditions. The validation results at the daily time scale showed an overall root mean square error (RMSE) of 30.34 W m −2 and an R value of 0.90 under clear sky conditions, whereas these values were 42.03 W m −2 and 0.86, respectively, under cloudy sky conditions. The DSR estimates had an overall RMSE value of 16.93 W m −2 and an R value of 0.97 at the monthly time scale. The Clouds and Earth's Radiant Energy System (CERES) Energy Balanced and Filled (EBAF) data sets were also used for comparison with the DSR estimates based on the GBRT method. The DSR estimates based on the GBRT method exhibited similar spatial distributions with those of the CERES-EBAF DSR product. Moreover, the DSR estimates based on the GBRT method did not show a clear overestimation tendency, as the CERES-EBAF DSR product did, at the CDC/CMA sites.